Spatial Analysis of The Needs of Green Open Space at Universitas Negeri Padang - Aliman, Muhammad; Yustesia, Arisius; Barlian, Eri; Syah, Nurhasan (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The decreasing of environmental quality in padang is caused by the changes of the land, the increasing number of vehicles and the increasing number of population. The solution to overcome these problems is by providing a green open space at universitas negeri padang (unp). The objectives of this study are 1) to analyze the needs of green open space at unp, 2) to plan the construction of open green space at unp. The method employed in this study was survey by using spatial analysis remote sensing data from google earth. The results of the study revealed that unp had open green space as large as 7.643 ha. The area of green open space at unp that fulfilled the width criteria was as much as 10%, and the fulfillment of population and clean air criteria was as much as 20%. However, the minimum width criterion of green open space, which was as much as 30%, was not fulfilled yet. The discrepancy between the area of open green space and the criteria of minimum width (30%) was 0.447 ha. Such lack of green open space can be filled by: optimizing the unoccupied land as large as 1.4 ha by planting the clump, providing 2308 flower’s pots, and making use of building shelter and building lobbies, and campus corridor to be planted with clump, ornamental plants or other types of epiphytes and lianas.